Analisis Inflansi dan Pengaruhnya terhadap Pertumbuhan Ekonomi di Kupang - Wea, Aqualina; Dhundu, Maria Gego; Lawalu, Emiliana Martuti (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
Inflation remains one of the critical macroeconomic challenges affecting regional economic stability, including in Kupang City. The city’s reliance on imported goods, inadequate infrastructure, and volatility in agricultural commodity prices make it particularly vulnerable to inflationary pressures. This study aims to analyze the impact of inflation on economic growth in Kupang by identifying key contributing factors and assessing their implications for macroeconomic performance. A qualitative method was employed using a literature review approach, drawing from empirical studies, policy documents, and theoretical frameworks on inflation and regional development. The analysis integrates public sector accounting perspectives to understand how local fiscal governance responds to inflation-related economic stress. The results indicate that inflation negatively affects household purchasing power, investment levels, and business certainty, thereby hampering economic growth. Furthermore, limitations in infrastructure and weak fiscal planning contribute to inefficient budget allocations and reduced responsiveness to inflationary trends. The study highlights the need for a more transparent and participatory budget planning process, enhanced fiscal control systems, and stronger inter-institutional coordination to mitigate the impact of inflation. These findings offer policy insights for local governments to formulate more effective strategies aimed at inflation control and long-term sustainable growth in Kupang.